Determination of Main Bearing Dynamic Clearance in a Shield Tunneling Machine Through a Broadband PMUT Array with a Decreased Blind Area and High Accuracy - Guoxi Luo; Haoyu Zhang; Delai Liu; Wenyan Li; Min Li; Zhikang Li; Lin Sun; Ping Yang; Ryutaro Maeda; Libo Zhao (Sensors)
Traditional PMUT ultrasonic ranging systems usually possess a large measurement blind area under the integrated transmit–receive mode, dramatically limiting its distance measurement in confined spaces, such as when determining the clearance of large bearing components. Here, a broadband PMUT rangefinder was designed by integrating six types of different cells with adjacent resonant frequencies into an array. Through overlapping and coupling of the bandwidths from the different cells, the proposed PMUTs showed a wide –6 dB fractional bandwidth of 108% in silicon oil. Due to the broadening of bandwidth, the device could obtain the maximum steady state with less excitation (5 cycles versus 14 cycles) and reduce its residual ring-down (ca. 6 μs versus 15 μs) compared with the traditional PMUT array with the same cells, resulting in a small blind area. The pulse–echo ranging experiments demonstrated that the blind area was effectively reduced to 4.4 mm in air or 12.8 mm in silicon oil, and the error was controlled within ±0.3 mm for distance measurements up to 250 mm. In addition, a specific ultrasound signal processing circuit with functions of transmitting, receiving, and processing ultrasonic waves was developed. Combining the processing circuit and PMUT device, the system was applied to determine the axial clearance of the main bearing in a tunneling machine. This work develops broadband PMUTs with a small blind area and high resolution for distance measurement in narrow and confined spaces, opening up a new path for ultrasonic ranging technology.